Expression Analysis in Multiple Muscle Groups and Serum Reveals Complexity in the MicroRNA Transcriptome of the mdx Mouse with Implications for Therapy - Thomas C Roberts; K Emelie M Blomberg; Graham McClorey; Samir EL Andaloussi; Caroline Godfrey; Corinne Betts; Thibault Coursindel; Michael J Gait; CI Edvard Smith; Matthew JA Wood (Elsevier, 2012)
MicroRNAs (miRNAs) are a class of small RNAs that regulate gene expression and are implicated in wide-ranging cellular processes and pathological conditions including Duchenne muscular dystrophy (DMD). We have compared differential miRNA expression in proximal and distal limb muscles, diaphragm, heart and serum in the mdx mouse relative to wild-type controls. Global transcriptome analysis revealed muscle-specific patterns of differential miRNA expression as well as a number of changes common between tissues, including previously identified dystromirs. In the case of miR-31 and miR-34c, upregulation of primary-miRNA transcripts, precursor hairpins and all mature miRNAs derived from the same transcript or miRNA cluster, strongly suggests transcriptional regulation of these miRNAs. The most striking differences in differential miRNA expression were between muscle tissue and serum. Specifically, miR-1, miR-133a, and miR-206 were highly abundant in mdx serum but downregulated or modestly upregulated in muscle, suggesting that these miRNAs are promising disease biomarkers. Indeed, the relative serum levels of these miRNAs were normalized in response to peptide-phosphorodiamidate morpholino oligonucleotide (PMO) mediated dystrophin restoration therapy. This study has revealed further complexity in the miRNA transcriptome of the mdx mouse, an understanding of which will be valuable in the development of novel therapeutics and for monitoring their efficacy.